Varying effectiveness of teaching versus class size - Ejsmont, Wiktor (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
In the article, the author attempts to measure the changing effectiveness of learning in different-sized classes in Poland. For this purpose, he uses models for panel data. The application of panel models for measuring effectiveness was launched by M. Aitkins and N. Longford in 1986. The author also introduces the concept of unevenness of teaching effectiveness. In the second part of the article he applies the data to the proper models and draws conclusions from the obtained results.
Mathemathical Economics, 2011, Nr 7 (14), s. 51-64
Keywords: school effectiveness; class size; analysis of panel data